Thailand Economic Monitor, July 2019 : Harnessing Fintech for Financial Inclusion - World Bank Group (World Bank, Bangkok, 2019)
The Thailand Economic Monitor (TEM) consists of two parts. Part 1 of the TEM reviews recent economic developments, examines the country’s macroeconomic outlook, and analyzes the impact of key policy changes. Part 2 focuses on a specific subject with critical implications for Thailand’s long-term growth prospects. This edition of the TEM analyzes the power of financial technology (fintech) to support financial inclusion, a key element of the 20-Year National Strategy.